Exosomes in transcellular proteostasis and Age-Related Macular Degeneration - Ferraz, Luís Filipe Mourão de Carvalho (2023)
Abstract Age-related macular degeneration (AMD) stands as one of the most common causes of blindness, affecting one in eight people over 60 years of age and more than 190 million individuals worldwide. With the aging of global population, these numbers are expected to surge. Alarmingly, there is still no effective treatments for the dry form of AMD, while the sole available treatment for its wet counterpart, which affects only 10% of patients, relies on VEGF inhibitors and can only delay disease progression. Therefore, there is an urgent need for new therapeutic strategies. AMD is characterized by progressive degeneration of the macula, a region with the densest photoreceptor population, and subsequent loss of the central and more detailed vision area. While AMD pathology mechanisms are yet to be fully understood, one defining aspect of the disease is the degeneration of the Retinal Pigment Epithelium (RPE). These postmitotic cells play a pivotal role since they are responsible for phagocytosing and degrading the shed apices of the photoreceptor outer segments (POS), as photoreceptors regenerate their visual pigment-laden extensions. Over time, because of the increased phagocytic burden, RPE cells in the macula face an increased proteolytic challenge, often resulting in localized degeneration within the macular region, with the surrounding peripheral retina remaining relatively preserved. The progressive loss of proteolytic capacity is one of the defining aspects of the age-related decline of Proteostasis. Proteostasis, or the mechanisms maintaining the balance between synthesis, folding, trafficking, and degradation of proteins, has been perceived as an inherently cell-autonomous process. However, therapies constructed on this supposition present severe limitations. In this context, researchers have recently pivoted towards the idea that proteostasis can be orchestrated in a broader, more systemic way, encompassing entire tissues and organs. An example of transcellular proteostasis is the potential exchange of proteostasis machinery and even undegraded, toxic proteins between cells via extracellular vesicles. Within this framework, AMD emerges as an ideal model to study the molecular mechanisms of transcellular proteostasis, mediated by extracellular vesicles, within the RPE monolayer. We hypothesize that extracellular vesicles may transfer proteostasis machinery from the more burdened macular RPE to the periphery and dispose of unwanted and undegraded proteins derived from incomplete POS elimination. Our data shows that a particular type of extracellular vesicles, exosomes, may participate in the clearance of harmful POS material that RPE cells cannot degrade. This mechanism may protect RPE cells from toxicity but also transfer proteotoxic peptides to other cells. Lamp2a, a membrane protein present in endosomes and lysosomes, was also identified as a potential regulator of the selective targeting of undegraded protein material into exosomes.